2008
DOI: 10.3141/2065-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reduction in Effective Capacities of High-Occupancy Vehicle Lanes Related to Traffic Behavior

Abstract: Previous research efforts have quantified the capacity of non-barrier-separated, high-occupancy vehicle (HOV) lanes. However, the majority of these efforts have focused on HOV lanes that usually operate well below capacity. In contrast, the I-85 HOV lanes in Atlanta, Georgia, usually operate under constrained flow conditions during morning and afternoon peak periods. This provides an opportunity to assess the relative performance of the HOV lane to the adjacent general-purpose (GP) lanes, which also undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Recently, slow speeds in a special‐use lane, such as a carpool or bus lane, were verified because of both high demands for that lane and slow speeds in the adjacent regular‐use lane . The dual influences were observed in buffer‐separated HOV lanes and the barrier separation . Safety concerns of HOV drivers associated with potential merging in and out the HOV lane are the main reasons.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, slow speeds in a special‐use lane, such as a carpool or bus lane, were verified because of both high demands for that lane and slow speeds in the adjacent regular‐use lane . The dual influences were observed in buffer‐separated HOV lanes and the barrier separation . Safety concerns of HOV drivers associated with potential merging in and out the HOV lane are the main reasons.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, dedicated lanes generate more complex traffic dynamics on freeway corridors. Friction effect has been observed on freeways with HOV lanes, characterized by the speed reduction on the HOV lane when the adjacent general purpose lane is congested [18][19][20]. Modeling the differences in lane usage and lane change between HOV and single occupancy vehicles is important to reproduce the traffic conditions around HOV lanes.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that in some areas, HOV lanes do not function properly, in that the lanes operate below capacity or the lanes become congested like their general purpose (GP) lane counterparts (3). HOT lanes promise to make better use of existing HOV lanes to provide capacity more efficiently than either conventional HOV lanes or GP lanes by managing demand.…”
mentioning
confidence: 99%